High-resolution near-infrared observations of NGC 1068 - Quirrenbach, A; Eckart, A; Thatte, N (1997)
We present near-infrared observations of NGC 1068 obtained with the SHARP camera at the ESO 3.5 m telescope, and with SHARP II attached to the COME-ONS adaptive optics system at the ESO 3.6 m telescope. From the SHARP observations we obtain a K band image of the stellar bar with O.'' 4 resolution, and an upper limit to the sire of the nuclear K band source of 0.'' 05 (3.5 pc). The adaptive optics observations are used to determine the position of the infrared nucleus with respect to the visible continuum. The centroid of the 5000 to 9000 Angstrom continuum is displaced 0.'' 23 +/- 0.'' 10 to the east and 0.'' 41 +/- 0.'' 10 to the north of the K band peak.